State-of-the-art optimization methods for short-term mine planning [version 2; peer review: 1 approved, 2 approved with reservations] - Nasib Al Habib; Moise Kambala Malundamene; Hooman Askari-Nasab; Khalil Abdessamad; Saâd Soulaimani (F1000Research)
Maintaining short-term planning aligned with the ultimate long-term plan is challenging. This requires many details to be modelled on a daily or weekly basis to reach this target. Short-term planning is more challenging than medium- and long-term planning because it deals with daily challenges with block model changes, mining cut polygons variation, which increases the gap between medium- and long-term plans for each material to be mined. Short-term mine planning teams are expected to identify and manage potential risks to mitigate them, and eventually achieve the long-term objective of maximizing the Net Present Value (NPV). Very few studies have identified the problems that exist in short-term mine planning and provided technical solutions to overcome them for open-pit mines. One of the complexities associated with short-term planning is the creation of polygons or mining cuts by clustering before optimizing and scheduling the plan to reduce the computational expense of mine planning models. The primary objective of this study is to review the latest papers describing short-term mine planning challenges and technical solutions proposed to optimize mine planning for open-pit mines.